Cellular Protein HAX1 Interacts with the Influenza A Virus PA Polymerase Subunit and Impedes Its Nuclear Translocation - Hsu, Wei-Bin (American Society for Microbiology, 2013)
Transcription and replication of the influenza A virus RNA genome occur in the nucleus through the viral RNA-dependent RNA polymerase consisting of PB1, PB2, and PA. Cellular factors that associate with the viral polymerase complex play important roles in these processes. To look for cellular factors that could associate with influenza A virus PA protein, we have carried out a yeast two-hybrid screen using a HeLa cell cDNA library. We identified six cellular proteins that may interact with PA. We focused our study on one of the new PA-interacting proteins, HAX1, a protein with antiapoptotic function. By using glutathione S-transferase pulldown and coimmunoprecipitation assays, we demonstrate that HAX1 specifically interacts with PA in vitro and in vivo and that HAX1 interacts with the nuclear localization signal domain of PA. Nuclear accumulation of PA was increased in HAX1-knockdown cells, and this phenotype could be reversed by reexpression of HAX1, indicating that HAX1 can impede nuclear transport of PA. As a consequence, knockdown of HAX1 resulted in a significant increase in virus yield and polymerase activity in a minigenome assay, and this phenotype could be reversed by reexpression of HAX1, indicating that HAX1 can inhibit influenza A virus propagation. Together, these results not only provide insight into the mechanism underlying nuclear transport of PA but also identify an intrinsic host factor that restricts influenza A virus infection.